Asuhan Keperawatan Pada Nn. N P1AO Post Sectio Caesarea Dengan Indikasi Ketuban Pecah Dini Di Ruang Bougenvile RS T IV Slamet Riyadi - Mursilowati, Tri, Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep (2015)
NURSING CARE Mrs.N WITH SECTIO CAESARIA P1A0 AMNIOTIC RUPTURE EARLY INDICATIONS IN BOUGENVILE WARD RS T IV SLAMET RIYADI SURAKARTA (Tri Mursilowati, 2015, 71 pages) ABSTRACT Background: Amniotic rupture early amniotic rupture is prematurely without any sign of inpartu and after an hour and still not follow with the process inpartu, as appropriate, so that sectio caesaria way out is to reduce the complications that occur. Objective: to know the nursing care on patients with indications sectio caesarea post amniotic rupture include early assessment, diagnosis, intervention, implementation, and evaluation of nursing. Results: After nursing actions performed during the 3x24 hours obtained results soreness patients reduced from 7 to 2, the scale does not occur any signs of infection, breast milk can not be fulfilled properly. Conclusion: the cooperation between the health team and the patient or family is indispensable for the success of the nursing care of the patients, the therapeutic communication can encourage patients more cooperative, so that the patient's nursing problems of pain, risk of infection, the ineffectiveness of breast feeding can be carried out in accordance with good intervention and most problems can be resolved in part. Keywords: sectio caesarea, amniotic rupture early, inpartu, ketidaefektifan breast feeding, the risk of infection.